Development of a head-eye coordinated robotic system - Fong, Chee Kong. (2008)
Computer vision systems have traditionally been designed without paying much attention to the observer role (camera motion, stereo system geometry, lens parameters, etc.) in the perceptual process. However, in recent years, researchers recovered the idea of active observer and active vision. From which intelligent robotic systems were built with advanced sensing capabilities that allow robots to adapt to changes in its environment without specific operator intervention. Motivated by similar context, the thesis attempts to describe the development of an empirical head-eye co-ordinated robot. Two objectives were drawn; (1) Design and development all the hardwares for a fully autonomous head-eye co-ordinated robot, which will include an Active Head and a Mobile Platform, and (2) Derive the kinematics for the proposed robotic system. As a result, an active head (NASH) mounted onto a fully computerized mobile platform (Omni-DAMP) were developed.